The anti-waggle dance: use of the stop signal as negative feedback - Kietzman, Parry M.; Visscher, P. Kirk (Frontiers in Ecology and Evolution, 2015)
Numerous activities within honey bee (Apis mellifera L.) colonies rely on feedback loops for organization at the group level. Classic examples of these self-organizing behaviors occur during foraging and swarm nest site selection. The waggle dance provides positive feedback, promoting foraging at a specific location or increased scouting at a potential nest site. Rather less well known than the waggle dance, the stop signal, a short vibration often delivered while butting against a dancing bee, is currently best understood as a counter to the waggle dance, offering negative feedback towards the advertised foraging location or nest site. When the stop signal is received by a waggle dancer she is more likely to terminate her dance early and retire from the dance floor. Bees that experienced danger or overcrowding at a food source are more likely to perform the stop signal upon their return to the colony, resulting in an inhibition of foraging at that location. During a swarm’s nest site selection process, scout bees that visited a different site than the one being advertised are more likely to stop-signal the waggle dancer than are scouts that had visited the same site. Over time, the scout bees build recruitment to a single site until a quorum is reached and the swarm can move to it. The balance between the positive feedback from the waggle dance and the negative feedback from the stop signal allows for a more sensitive adjustment of response from the colony as a unit. Many of the processes associated with the feedback loops organizing a honey bee colony’s activities are in striking parallel to other systems, such as intercellular interactions involved in motor neuron function.